Interconnection of Family Functions and Child Education in the Perspective of Hadith - Syarif, Maria Ulfah; Mardhati, Mardhati; Syarif, Rasdiyanah Audiah; Asse, Ambo; Yahya, Muhammad (Al-Bayyinah, 2023)
The family becomes an institution capable of giving birth to the next generation (offspring) who are intelligent and have good morals (good character) both in the eyes of their own family, especially in the eyes of the surrounding community. However, along with the times, accompanied by the rapid development of science and digitalization technology, the family has now lost responsibility as the first education. This study aims to explore the function of the family in providing education, through the perspective of hadith. This research uses the type of library research, which is a series of activities related to the method of collecting library data by making texts into texts from several literatures. Specifically, this research collects documents from hadith books related to family functions and children's education. The results of this study indicate that the hadiths about family education provide an understanding that basically every child who is born is born in a state of nature, clean and holy from sins. It is just that the environment where he lives and the school environment where he lives makes it easy to give a bad influence if it is not balanced with the education of his family.Â